Assessment of the cellular integrity and expression of melatonin receptor (MTNR1A) in the retina assaulted by ethanol and acetaminophen. (22nd December 2022) - Adekeye, AO; Fafure, AA
Ethanol exposures have been reported to disrupt the development of the retina and optic nerve which can be considered as part of underlying mechanisms of visual pathway impairments. This study aims to investigate the cellular integrity of the retina and the expression of melatonin receptor (MTNR1A) in the retina when assaulted chronically and simultaneously by ethanol and acetaminophen. Animals were randomly grouped into five groups. Control (normal saline), Alcohol group (25% alcohol in 2% sucrose solution), Acetaminophen group, (100 mg/kg BW for 14 days), Acetaminophen + Alcohol group (25% alcohol in 2% sucrose solution + 100 mg/kg BW of paracetamol). Withdrawal group (25% alcohol in 2% sucrose solution + 100 mg/kg BW of paracetamol). The body weight and rectal temperature of the animals were taking every 2 days and a post mortem study was conducted by quantitatively assessing the markers of oxidative stress. Melatonin level was quantified in the retina tissue and Immunohistochemistry was done via MTNR1A to study the expression of melatonin receptor type 1A in the retina. These results demonstrate that alcohol and acetaminophen significantly reduced the activity of retina rat melatonin (MTNR1A) levels, lowers the SOD and MDA activity. Expression of MTNR1A was reduced in the ganglionic cell layer of Alcohol and acetaminophen group as compared to the control and withdrawal group. It can be inferred that chronic simultaneous intake/consumption of alcohol and acetaminophen altered the melatonin level in the retina and this may implicate the circadian clock and melatonin in Wistar rat visual system.